Cationic Pb2 Dumbbells Stabilized in the Highly Covalent Lead Nitridosilicate Pb2Si5N8. (3rd January 2019) - Bielec, Philipp; Nelson, Ryky; Stoffel, Ralf P.; Eisenburger, Lucien; Günther, Daniel; Henß, Ann‐Kathrin; Wright, Jonathan P.; Oeckler, Oliver; Dronskowski, Richard; Schnick, Wolfgang
Abstract: Due to the weak oxidative force of N2, nitrides are only typically formed with the less electronegative metals. Meeting this challenge, we here present Pb2 Si5 N8, the first nitridosilicate containing highly electron‐affine cations of a metal from the right side of the Zintl border. By using advanced synchrotron X‐ray diffraction, the crystal structure was determined from a tiny single crystal of 1×3×3 μm 3 in size, revealing a significantly different bonding situation compared to all other nitridosilicates known so far. Indeed, DFT calculations confirm distinct amounts of covalency not only between Pb and N but also between formal Pb 2+ cations. Thus, unprecedented cationic Pb2 dumbbells with a stretching vibration at 117 cm −1 were found in Pb2 Si5 N8, the first representative of a crystallographically elucidated lead nitride, stabilized by high amounts of covalency.